Clinical simulation with cyber patients in nursing education: a scoping review - de Queiroz Xavier, Bárbara Letícia; Rodrigues de Oliveira, Vinícius; Targino Ferreira, Thais; Lilian Costa Firmino Segundo, Larissa; Fernandes de Freitas, Yasmim Yngrid; Augusto Rosendo Da Silva, Richardson (Frontiers in Education, 2025)
This study aimed to identify and map the existing evidence on clinical simulation with cyber patients in order to determine whether this strategy can fill existing scientific gaps and clarify its use in the teaching and learning process in nursing education. This is a scoping review, with a protocol registered on the Open Science Framework (OSF), DOI 10.17605/OSF.IO/GAXR6. For the development of this review, the guidelines and steps outlined in the Joanna Briggs Institute (JBI) Reviewer's Manual were followed. The search was conducted across 13 national and international databases. Articles, dissertations, and theses that addressed the academic training of nursing students using cyber patient simulation studies were selected, with no restrictions regarding location, time, or language. These studies were subsequently analyzed by two independent reviewers, with a third reviewer added to make the final decision. The final sample consisted of 24 studies out of the initial 6,669 identified, the majority of which originated from developed and developing countries. None of the selected studies specified the curriculum component in which clinical simulation was used, nor whether there was an interest in linking it to specific curricular components. Regarding the skills targeted through simulation, the main ones identified were: clinical, practical, communication, decision-making, and critical thinking skills. It can be inferred that simulation with cyber patients allows students to learn from mistakes without compromising patient safety and fosters the development of critical thinking, satisfaction, and self-confidence. Additionally, it presents a favorable cost-benefit ratio, as it proved to be a more affordable option compared to mannequin-based simulation.